2020
DOI: 10.1371/journal.pone.0230186
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of professionalism between emergency medicine resident physicians and faculty physicians: A multicenter cross-sectional study

Abstract: Professionalism is a critical competency for emergency medicine (EM) physicians, and professional behavior affects patient satisfaction. However, the findings of various studies indicate that there are differences in the interpretation of professionalism among EM resident physicians and faculty physicians. Using a cross-sectional survey, we aimed to analyze common challenges to medical professionalism for Japanese EM physicians and survey the extent of professionalism coursework completed during undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…There was no absolute cultural consensus among healthcare providers and patients. Previous studies examined EPP perceptions in one or a few groups of participants [17][18][19]. The present study aimed to simultaneously assess the EPP viewpoints from all related persons in EDs (healthcare providers and patients) to assess 360-degree perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…There was no absolute cultural consensus among healthcare providers and patients. Previous studies examined EPP perceptions in one or a few groups of participants [17][18][19]. The present study aimed to simultaneously assess the EPP viewpoints from all related persons in EDs (healthcare providers and patients) to assess 360-degree perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…Most health professionals are well aware of professionalism and its impact on medical education and clinical practice [ 31 ]. In a study in Japan, emergency medicine (EM) residents scored higher than EM physicians when questioned about confidentiality and sexual harassment [ 32 ]. Another study showed that clinical groups of students scored higher than preclinical students in a quiz about professionalism.…”
Section: Reviewmentioning
confidence: 99%
“…It is also important to understand that the PDs and other educators could play a fundamental role in the residents' performances, ranging from considering those educators as role models, to continuously assessing and delivering sufficient feedback. Several studies have been conducted regarding residents' performances, but none addressed the direct effect of educators on their residents' performances [2][3][4][5]. The lack of studies about the direct effect of educators on the performance of residents is a major gap within the academic literature.…”
Section: Introductionmentioning
confidence: 99%
“…After an extensive search in the literature review, no study was found addressing the direct influence of EM educators on their residents' academic and clinical performances [2][3][4][5]. The lack of research about the influence of EM educators on their residents is problematic given the importance of these individuals in training EM residents.…”
Section: Introductionmentioning
confidence: 99%